Creating a Community Cloud: Leveraging Open-Source Software for the Mennonite Archival Information Database - Stoesz, Conrad; Hildebrand, Jason; Bak, Greg (Archivaria, 2024)
Developing and sustaining digital infrastructure is challenging for small community archives. The promise of open-source technologies can seem elusive for those faced with the steep development costs of implementing and configuring new systems and migrating data from legacy systems. When community archives co-operate by forming consortia, the costs and challenges of development, implementation, and migration can be mitigated and shared. We offer a case study of the development of an open-source Access to Memory (AtoM) database among a consortium of Mennonite archives.